Pengaruh Sosialisasi, Kualitas Pelayanan, Sanksi dan Biaya Kepatuhan Pada Tingkat Kepatuhan Wajib Pajak Kendaraan Bermotor - Dewi, Ni Komang Ayu Puspita; Jati, I Ketut (E-Jurnal Akuntansi; Vol 25 No 1 (2018)DO - 10.24843/EJA.2018.v25.i01.p01, 2018)
Tax compliance is a situation where in accordance with the applicable law must meet the obligations of taxpayers and taxation rights. This research has the goal to test and obtain proof of whether socialization, quality of service, tax penalties, and compliance costs have an impact on the level of tax compliance vehicles. The study was conducted at the Joint Office SAMSAT Klungkung. method Accidental sampling is a method which is used to determine the sample that will be used by the sample size was calculated based on the Slovin formula. Data was collected by interview and disseminate questionnaire to 100 respondents. Multiple Linear Regression analysis is a technique used in this study. This study gives the results of socialization variables, quality of service, and tax penalties have a positive and significant impact on taxpayer compliance motor vehicle, but the variable cost of compliance has a negative effect on the rate of motor vehicle tax compliance. Keywords: Socialization Taxation, Quality of Service, Tax Penalties, Compliance Costs, Compliance Taxpayer